2018
DOI: 10.1111/joor.12732
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial pain assessment and management for patients with dementia: A meta‐ethnography

Abstract: Delivering dental treatment for patients with dementia can be challenging, and the complexity of treatment provision can increase as dementia progresses. Treatment at the later stages of dementia can be associated with ethical challenges and procedural risk meaning that a comprehensive patient assessment is crucial; the presence of orofacial pain is a key indication for active intervention from dental teams. To explore the process of oro-facial pain assessment and management, a comprehensive review of qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In line with this finding, many GPs questioned the 'reliability' or 'accuracy' of self-report pain tools for people with dementia. This finding is reflected in previous qualitative literature, in which nurses perceived pain assessment as a 'complex process', 50,51 with reduced or altered verbal communication as a key barrier to pain assessment, 30 and the use of self-report tools. 27,52 Identifying behavioural, psychological, and physical changes has previously been recognised as a key strategy to build a picture of the pain experience.…”
Section: Comparison With Existing Literaturementioning
confidence: 52%
See 3 more Smart Citations
“…In line with this finding, many GPs questioned the 'reliability' or 'accuracy' of self-report pain tools for people with dementia. This finding is reflected in previous qualitative literature, in which nurses perceived pain assessment as a 'complex process', 50,51 with reduced or altered verbal communication as a key barrier to pain assessment, 30 and the use of self-report tools. 27,52 Identifying behavioural, psychological, and physical changes has previously been recognised as a key strategy to build a picture of the pain experience.…”
Section: Comparison With Existing Literaturementioning
confidence: 52%
“…27,52 Identifying behavioural, psychological, and physical changes has previously been recognised as a key strategy to build a picture of the pain experience. 30,49 However, in this study, GPs often found it challenging to determine if pain was the driver of behavioural or psychological changes. This challenge may be intensified as many GPs in this study were unaware of and/or did not use behavioural observation pain tools, despite being recommended by UK guidelines.…”
Section: Comparison With Existing Literaturementioning
confidence: 86%
See 2 more Smart Citations
“…These stakeholders raised concerns about living with pain which may not be identifiable; a paper was co-written with a carer helping to explore the published research about this problem. 1 Patients also expressed concern about needing complicated treatment when they were too unwell to cope with it or when dental treatment might lead to more harm than benefit.…”
mentioning
confidence: 99%